Proces powstawania Kliniki Chorób Oczu Akademii Medycznej w Łodzi, etapy jej rozwoju i działalność w latach 1945-1970 - Grącka, Joanna (Klinika Oczna / Acta Ophthalmologica Polonica, 2009)
The paper tackles the beginnings of the Lodz Eye Clinic and provides information about its premises and staff. It also concerns the development of the clinic, incorporating the medical equipment, enlarging the services’ variety and the employment of the new staff. The paper provides some information about the activities of the Clinic, like consultations, surgeries, educating medical students and nurses, and exchanging the research views with other specialists during the conferences. The author paid much attention to the research done by the doctors from the Lodz Eye Clinic and their achievements presented at various conferences and those which were published.